Factors associated with hepatitis C treatment adherence: an integrative review - Côco, Layla Tatiane [UNESP]; Silva, Giovanni Faria [UNESP]; Romeiro, Fernando Gomes [UNESP]; Cerqueira, Ana Teresa de Abreu Ramos [UNESP] (FapUNIFESP (SciELO), 2022)
This integrative review examined factors associated with hepatitis C treatment adherence. The articles included were published in English, Spanish and Portuguese in the Lilacs, Medline, PsycINFO, Web of Science, Scopus and CINAHL databases, between 2000 and 2019. Initially, 540 publications were found and, after applying the study inclusion criteria, 22 articles were selected. Percentage non-adherence to treatment ranged from 12% to 32%. The variables identified as facilitating adherence were: Receiving treatment for psychiatric disorders identified during treatment; knowing about medications and disease; receiving less complex treatment with greater likelihood of cure; fewer adverse events; social support; doctor-patient communication; and/ or being in relationships. Barriers to adherence identified were: Presence of depressive symptoms and other mental disorders; abuse of alcohol and psychoactive substances; education; age; ethnicity; unemployment; not having a steady partner; stigma; distance from health services; and the complexity and adverse effects of treatment. This review identified gaps in research on adherence.
Keywords: Hepatitis C; Review; Treatment adherence